MODEL PEMBELAJARAN DISCOVERY LEARNING UNTUK MENINGKATKAN HASIL BELAJAR PESERTA DIDIK MATA PELAJARAN AKUNTANSI - Budi Mulyati; Idmi Idmi; Siti Arfiyanah (Progress: Jurnal Pendidikan, Akuntansi dan Keuangan, 2018)
This research was aimed to improve the accounting learning result using Discovery Learning Model for student in class XI SMK Al- Insan Cilegon. This research used class room action research method with two cycles. Each cycle had four steps: planning, action, observing and reflection. The research subject were 45 students and the teacher as the collaborator team.The research results showed that discovery learning model could improve the student learning achievement because, at first cycle, from 45 students, almost 66.7% (30 students) could achieve the minimum score and at the second cycle all student achieved the minimum score.